A pedagogia histórico-crítica durante o governo Jaime Lerner no Paraná (1995-2002) - Moreira, Helloysa Bragueto (2016)
This dissertation is the result of studies on the Historical-Critical Pedagogy (HCP), with the time delimitation the period 1995 to 2002. The issue of research starts from the assumption that Historical-Critical pedagogical theory was present in educational discussions of Paraná state during a consistent period, it started in the management of José Richa (1983-1987), having continuity in Álvaro Dias government (1988-1990) and ended in Roberto Requiao's administration (1991-1994). Thus, from the publication of the Currículo Básico para a Escola Pública do Estado do Paraná - CBEP (Basic Curriculum for Public School of Paraná) in 1990, the idea has spread that HCP was the pedagogical concept of this document and therefore theoretical foundation of the state's schools. Thereby, from the government Jaime Lerner, this concept would have been supplanted by other pedagogical proposals. From there, we question whether there was a movement against the HCP in the period in which the state of Paraná was governed by Jaime Lerner. In front of this problem, we try to verify how it developed, what features assumed the HCP in Parana during what is known as a major neoliberal governments that the state ever had. We emphasize first that from the research taken as a reference, it is possible to assert that the Historical-Critical Pedagogy is not expressed in the CBEP, and also not consolidated as pedagogical theory of the state. Still, with the publication of Curriculum Basic in 1990, Roberto Requião took office at the time of implementation of this proposal. However, Requião stimulated plurality of pedagogical concepts, educational innovations, school autonomy and the theory of citizen school thus, did not allow the continuation of discussions about HCP. What was evident is that there was a dislocation in CBEP organization process even at the time of preparation, which continued most acutely from Roberto Requiao government when it "shelved" the curriculum, and ended in government Jaime Lerner, by the implementation of an educational policy that distanced much of the historical-critical pedagogical theory.